2021
DOI: 10.1186/s12913-021-07349-5
|View full text |Cite
|
Sign up to set email alerts
|

Medication discrepancies among hospitalized patients with hypertension: assessment of prevalence and risk factors

Abstract: Background Medication errors remained among the top 10 leading causes of death worldwide. Furthermore, a high percentage of medication errors are classified as medication discrepancies. This study aimed to identify and quantify the different types of unintentional medication discrepancies among hospitalized hypertensive patients; it also explored the predictors of unintentional medication discrepancies among this cohort of patients. Methods This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…For example, a patient could have seen an outside clinician who changed the medication regimen between the last pre-admission visit and admission. Similarly, administrative 13 This article is protected by copyright. All rights reserved.…”
Section: Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a patient could have seen an outside clinician who changed the medication regimen between the last pre-admission visit and admission. Similarly, administrative 13 This article is protected by copyright. All rights reserved.…”
Section: Manuscriptmentioning
confidence: 99%
“…Previous studies have shown that discrepancies are highly prevalent among populations of hypertensive patients. 13,14 We hypothesized that this kind of medication discrepancy is prevalent regardless of disease type.…”
Section: Background and Significancementioning
confidence: 99%
“…Commission; medication without clear indication. different dose; dose varying from pre-admission prescription medication dose [9,10,11,12,13].…”
Section: Operational De Nition and De Nition Of Termsmentioning
confidence: 99%
“…9 As a result, medication safety has gained increased attention and is considered a global issue. 10 Medication errors may occur at all stages including prescribing, transcribing, supply, and administration. 11 The latter, in particular, is one of the common and susceptible stages to encounter frequent errors.…”
Section: Introductionmentioning
confidence: 99%
“…9 As a result, medication safety has gained increased attention and is considered a global issue. 10…”
Section: Introductionmentioning
confidence: 99%